2018
DOI: 10.1075/lab.16015.jia
|View full text |Cite
|
Sign up to set email alerts
|

The acquisition of relative clauses by Mandarin heritage language children

Abstract: This study examined the phenomena of incomplete acquisition, attrition, and protracted acquisition of the L1 in HL children by focusing on the comprehension and production of subject and object relative clauses (RCs) in Mandarin HL children. A cross-sectional design (study 1) and a longitudinal design (study 2) were both included. Our results showed that HL children were comparable to monolinguals for the comprehension of RCs in both study 1 and 2. For the production of RCs, although monolinguals outperformed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 44 publications
3
26
0
Order By: Relevance
“…Past research on monolingual acquisition has produced an inconsistent pattern of results, which we have argued is for a large part due to methodological problems. There is also very little data on the topic from multilingual children (though see Chan et al, 2017;Jia & Paradis, 2018). Our results suggest that, for the comprehension of transitive RCs containing two animate nouns, there is a reliable subject RC preference in both monolingual and bilingual Mandarin-speaking children, which we have argued reflects a general preference to process early occurring nouns as agents and language-specific distributional frequencies that favor relativization on subjects.…”
Section: Discussionmentioning
confidence: 66%
“…Past research on monolingual acquisition has produced an inconsistent pattern of results, which we have argued is for a large part due to methodological problems. There is also very little data on the topic from multilingual children (though see Chan et al, 2017;Jia & Paradis, 2018). Our results suggest that, for the comprehension of transitive RCs containing two animate nouns, there is a reliable subject RC preference in both monolingual and bilingual Mandarin-speaking children, which we have argued reflects a general preference to process early occurring nouns as agents and language-specific distributional frequencies that favor relativization on subjects.…”
Section: Discussionmentioning
confidence: 66%
“…Pham and Tipton (2018) found that phonological short-term memory predicted both English and Vietnamese vocabulary in bilingual children aged 5–8 years in the United States. Jia and Paradis (2018) also found that individual differences in phonological short-term memory were associated with bilingual children’s syntactic abilities in L1 Mandarin.…”
Section: Age Cognitive Factors and Bilingual Developmentmentioning
confidence: 95%
“…Furthermore, younger heritage language children have had less exposure to the language than their older peers/siblings, and so age at testing is also an important factor (Flores et al, 2017). Older age and AOA were associated with stronger L1 narrative and complex syntax abilities in Mandarin L1–English L2 school-age children in Canada (Jia & Paradis, 2015, 2018). Flores et al (2017) also found that performance on a task measuring Portuguese morphosyntax in Portuguese–German children and youth increased with age.…”
Section: Age Cognitive Factors and Bilingual Developmentmentioning
confidence: 99%
“…The comprehension of RCs by dual-language children has been investigated in a number of studies (e.g., Garraffa et al, 2015;Hopp et al, 2019). Here, we concentrate on the studies focused on language pairs whose RCs have opposite orders, namely, head-initial RCs (such as English and Italian) vs. head-final RCs (such as Mandarin, Cantonese, and Korean) (e.g., Lee and Lee, 2004;Kidd et al, 2015;Chan et al, 2017;Hu and Guasti, 2017;Tsoi et al, 2019;Jia and Paradis, 2020). As we will see, these studies provide an inconsistent picture, either a subject/object asymmetry or no asymmetry being reported in dual-language acquisition; the error patterns of dual-language children are different from that of monolingual children, but it is not clear how this difference is related to length of exposure and thus to transfer effects.…”
Section: Relative Clauses In Dual-language Childrenmentioning
confidence: 99%
“…Two other relevant studies investigating Mandarin RC comprehension are Tsoi et al (2019) and Jia and Paradis (2020), both testing Mandarin-English dual-language children, but showing a different comprehension pattern. Jia and Paradis (2020) showed that dual-language school-aged children (M = 8;0) in Canada were comparable to monolingual Mandarin-speaking children (M = 7;1) in comprehending subject and object RCs. However, their dual-language children were older than their monolingual children.…”
Section: Relative Clauses In Dual-language Childrenmentioning
confidence: 99%